Modular Structured Multilevel Inverter with Unified Constant-Frequency Integration Control for Active Power Filters - Azli, N. A. (2005)
The increasing use of power electronics based loads in recent years has resulted in the generation of harmonic and reactive currents to the common point of coupling at which the loads are connected to. Besides the commonly used passive filters, active power filters (APFs) are gaining interest lately in canceling the reactive and harmonic currents from the nonlinear loads to ensure that the resulting total current drawn from the main incoming supply is sinusoidal. This paper presents a non- conventional inverter topology known as the Modular Structured Multilevel Inverter (MSMI) as an active power filter. With the MSMI, the harmonic content generated by the APF can be reduced as it can produce more levels of voltage than conventional inverters. Additionally, it can reduce the voltage and current ratings of the power devices used while providing the convenience for future expansion in order to achieve higher power ratings for the APF system. A Unified Constant-Frequency Integration (UCI) control technique is adopted for the MSMI APF which features constant switching frequency operation and simple analog circuitry. To demonstrate the capability of the proposed APF system, simulation results of a single-phase MSMI APF with UCI controller is presented and its performance analyzed.